2018
DOI: 10.1155/2018/3763084
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Eosinophilic Granulomatosis with Polyangiitis Complicated with A IgG4 Related Disease Like Symptoms

Abstract: We report a case of eosinophilic granulomatosis with polyangiitis (EGPA) complicated with a IgG4 related disease like symptoms presenting as eyelid swellings. In the present case, the serum level of IgG4 and the ratio of IgG4 to IgG were generally increased by the disease course of EGPA. Considering the course of clinical symptoms, there is a possibility that orbital manifestations were one of the clinical features during the disease course of EGPA while the histological features of right eyelid tissue and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…EGPA may be also accompanied by elevated serum IgG4 levels. Several studies have showed elevated serum IgG4 level [10, 11] and/or infiltration of IgG4-positive plasma cell in the tissue biopsy, two crucial features in patients with IgG4-RD, among EGPA patients [12, 13]. Nobuhiro et al described a EGPA case with a similar clinical condition of IgG4-related kidney disease, in which the patient was involved with a high serum IgG4 level, salivary gland swelling, tubulointerstitial nephropathy and infiltrate of IgG4 positive plasmacytes in the renal tissue, although the ratio of IgG4+ plasma cells to all IgG+ plasma cells is about 10% (less than 40%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EGPA may be also accompanied by elevated serum IgG4 levels. Several studies have showed elevated serum IgG4 level [10, 11] and/or infiltration of IgG4-positive plasma cell in the tissue biopsy, two crucial features in patients with IgG4-RD, among EGPA patients [12, 13]. Nobuhiro et al described a EGPA case with a similar clinical condition of IgG4-related kidney disease, in which the patient was involved with a high serum IgG4 level, salivary gland swelling, tubulointerstitial nephropathy and infiltrate of IgG4 positive plasmacytes in the renal tissue, although the ratio of IgG4+ plasma cells to all IgG+ plasma cells is about 10% (less than 40%).…”
Section: Discussionmentioning
confidence: 99%
“…Nobuhiro et al described a EGPA case with a similar clinical condition of IgG4-related kidney disease, in which the patient was involved with a high serum IgG4 level, salivary gland swelling, tubulointerstitial nephropathy and infiltrate of IgG4 positive plasmacytes in the renal tissue, although the ratio of IgG4+ plasma cells to all IgG+ plasma cells is about 10% (less than 40%). Suguru et al presented a case showing numerous infiltration of IgG4-positive plasma cells (about 50%) in the right upper eyelid and high serum IgG4 concentration (119 mg/dl) during the disease course of EGPA [13]. Besides, the ratio of serum IgG4 to IgG and IgG4 levels were elevated in the disease course.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown elevated serum IgG4 levels[ 3 ] and/or tissue infiltration with IgG4-positive plasma cells in the pathological examination of biopsy material in patients with EGPA. [ 4 , 5 ] Severe eosinophilia and elevated immunoglobulin E (IgE) levels, which are the typical features of EGPA, are also often observed in patients with IgG4-assosiated disease (IgG4-AD). [ 6 , 7 ]…”
mentioning
confidence: 99%